2005
DOI: 10.1158/0008-5472.can-04-4472
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Radiolabeled Engineered Anti-p185HER2 Antibody Fragments forIn vivoImaging

Abstract: We have recently described the in vivo properties of an iodinated anti-p185 HER2 engineered antibody fragment [minibody (scFv-C H 3) 2 ; 80 kDa], made from the internalizing 10H8 monoclonal antibody. Although the 10H8 minibody showed excellent binding to the target in vitro, only modest tumor uptake [5.6 F 1.7% injected dose per gram (ID/g) of tissue] was achieved in nude mice bearing MCF7/HER2 breast cancer tumors. Here, in an attempt to improve targeting, the 10H8 minibody was conjugated to 1,4,7,10-tetraaza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 39 publications
3
106
0
Order By: Relevance
“…We have shown that SarAr conjugation to both murine and chimerized mAb can be accomplished under nearly physiological conditions with no adverse affect on immunoreactivity. Incubation of the immunoconjugate with 64 Cu 2ϩ for 10-30 min results in nearly quantitative uptake of 64 Cu 2ϩ without the need for additional HPLC purification, yielding specific activities of Ϸ10 Ci/ g (Ϸ37 MBq/100 g), 2-3 times greater than previously published results using other chelating agents (9,25,26). Furthermore, these high specific activities were achieved without the need for postlabeling purification, as is required with other chelators.…”
Section: Discussionmentioning
confidence: 77%
“…We have shown that SarAr conjugation to both murine and chimerized mAb can be accomplished under nearly physiological conditions with no adverse affect on immunoreactivity. Incubation of the immunoconjugate with 64 Cu 2ϩ for 10-30 min results in nearly quantitative uptake of 64 Cu 2ϩ without the need for additional HPLC purification, yielding specific activities of Ϸ10 Ci/ g (Ϸ37 MBq/100 g), 2-3 times greater than previously published results using other chelating agents (9,25,26). Furthermore, these high specific activities were achieved without the need for postlabeling purification, as is required with other chelators.…”
Section: Discussionmentioning
confidence: 77%
“…Improved tumor localization has also been reported for other multimeric antibody formats (22,23,27,29,30,36,73) compared with their monomeric counterparts, although the use of different labeling methods, antigens and tumor types essentially precludes the direct and quantitative comparison of the data. However, what is fairly comparable to our finding is the biodistribution study of the 4D5 barnase-barstar miniantibodies (33), which only varies from our studies in the oligomerization modules used.…”
Section: Constructmentioning
confidence: 98%
“…On the other hand, large molecules, such as whole IgGs, show poor extravasation and slower tissue diffusion (20,21). At the same time, they can exhibit prolonged serum half-lives of up to several weeks (19), because they avoid renal excretion and are instead removed by the more delayed hepatic clearance (22). The resulting high serum concentration favors accumulation in the tumor, but also unspecific localization in non-target tissues.…”
mentioning
confidence: 99%
“…We used benzyl-DTPA in a previous study because of the easy and quick labeling at room temperature. Some publications (27,28) suggest that the use of DOTA derivatives requires heating up to 100˚C for efficient indium labeling, and that labeling at lower temperatures is rather inefficient (29). On the other hand, the gallium-DTPA complex is not considered to be sufficiently stable in vivo (30), and the use of PET with 68 Ga-labeled Z HER2:342 for visualization of HER2 would require the use of a macrocyclic chelator.…”
Section: Introductionmentioning
confidence: 99%